STAT3‐dependent analysis reveals PDK4 as independent predictor of recurrence in prostate cancer. Issue 4 (23rd April 2020) - Oberhuber, Monika; Pecoraro, Matteo; Rusz, Mate; Oberhuber, Georg; Wieselberg, Maritta; Haslinger, Peter; Gurnhofer, Elisabeth; Schlederer, Michaela; Limberger, Tanja; Lagger, Sabine; Pencik, Jan; Kodajova, Petra; et al.
Abstract: Prostate cancer (PCa) has a broad spectrum of clinical behavior; hence, biomarkers are urgently needed for risk stratification. Here, we aim to find potential biomarkers for risk stratification, by utilizing a gene co‐expression network of transcriptomics data in addition to laser‐microdissected proteomics from human and murine prostate FFPE samples. We show up‐regulation of oxidative phosphorylation (OXPHOS) in PCa on the transcriptomic level and up‐regulation of the TCA cycle/OXPHOS on the proteomic level, which is inversely correlated to STAT3 expression. We hereby identify gene expression of pyruvate dehydrogenase kinase 4 ( PDK4 ), a key regulator of the TCA cycle, as a promising independent prognostic marker in PCa. PDK4 predicts disease recurrence independent of diagnostic risk factors such as grading, staging, and PSA level. Therefore, low PDK4 is a promising marker for PCa with dismal prognosis. Synopsis: Transcriptomic and proteomic analyses in prostate cancer (PCa) reveal high TCA/OXPHOS activity and low PDK4 expression in low STAT3 tumors. PDK4 is a promising independent predictor of biochemical recurrence in PCa. Low STAT3 tumors show enhanced TCA/OXPHOS and ribosome activity in a gene co‐expression network and in transcriptomic and proteomic analyses. Enhanced ribosome‐ and metabolic activity is found in mice with a deletion of Pten and Stat3 in the prostate epithelium. Low STAT3 is associated with low PDK4 expression. PDK4 is an important regulator of TCA/OXPHOS. Analysis of patient data indicates that low PDK4 correlates with earlier biochemical recurrence in PCa. Abstract : Transcriptomic and proteomic analyses in prostate cancer (PCa) reveal high TCA/OXPHOS activity and low PDK4 expression in low STAT3 tumors. PDK4 is a promising independent predictor of biochemical recurrence in PCa.